Teaching virtues, forming values through the visual arts - Ramirez, Veronica E. (Anvil, 2007)
"This book is best for grade school teachers who integrate arts and virtues in their teaching. The discussion on the elements of art renders them the tools for teaching children how to view artworks. The modules on art-making, which are infused with the necessary virtues and values, will enable children to deepen their learning and to help in their formation as good persons."--Back cover.